2015
DOI: 10.1103/physrevb.92.024502
|View full text |Cite
|
Sign up to set email alerts
|

Orbital angular momentum in a nonchiral topological superconductor

Abstract: We investigate the bulk orbital angular momentum in a two-dimensional time-reversal broken topological superconductor with the Rashba spin-orbit interaction, the Zeeman interaction, and the s-wave pairing potential. Prior to the topological phase transition, we find the crossover from s wave to p wave. For the large spin-orbit interaction, even in the topological phase, L z /N does not reach −1/2, which is the intrinsic value in chiral pwave superconductors. Here L z and N are the bulk orbital angular momentum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 35 publications
(65 reference statements)
2
28
0
Order By: Relevance
“…The connection between angular momentum and spectral flow is, however, absent for example in the artificial p-wave model studied in Ref. [32] by Shitade and Nagai. They found that in the artificial p-wave model, achieved through the interplay of the s-wave proximity effect, the Rashba effect, and Zeeman field, angular momentum changes continuously even when the gap remains open and no states cross the zero energy.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between angular momentum and spectral flow is, however, absent for example in the artificial p-wave model studied in Ref. [32] by Shitade and Nagai. They found that in the artificial p-wave model, achieved through the interplay of the s-wave proximity effect, the Rashba effect, and Zeeman field, angular momentum changes continuously even when the gap remains open and no states cross the zero energy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is not immediately obvious how to map out chirality-based order parameters 15,52 from the sole order parameter in the model that is of s-wave pairing symmetry. The chiral nature of 2D s-wave TSC states and the role that the angular momentum carried by Cooper pairs plays in determining various properties of the system are to be explored in further detail in a future publication.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although the Fermi surface has a certain chirality (spin winding), in principle the two intrinsic chiralities are always present in a 2D s-wave TSC state. 15 It is known that in a spin-triplet chiral p-wave superconductor, vortices in the p x + ip y and p x − ip y states, which are degenerate at zero field, are not equivalent.…”
Section: -11mentioning
confidence: 99%
See 2 more Smart Citations